Thermal Tolerance of Zymomonas mobilis: Temperature-Induced Changes in Membrane Composition - Benschoter, A. S. (1986)
The membrane composition of Zymomonas mobilis changed dramatically in response to growth temperature. With increasing temperature, the proportion of vaccenic acid declined with an increase in myristic acid, the proportion of phosphatidylcholine and cardiolipin increased with decreases in phosphatidylethanolamine and phosphatidylglycerol, and the phospholipid/protein ratio of the membrane declined. These changes in membrane composition were correlated with changes in thermal tolerance and with changes in membrane fluidity. Cells grown at 20°C were more sensitive to inactivation at 45°C than were cells grown at 30°C, as expected. However, cells grown at 41°C (near the maximal growth temperature for Z. mobilis) were hypersensitive to thermal inactivation, suggesting that cells may be damaged during growth at this temperature. When cells were held at 45°C, soluble proteins from cells grown at 41°C were rapidly lost into the surrounding buffer in contrast to cells grown at lower temperatures. The synthesis of phospholipid-deficient membranes during growth at 41°C was proposed as being responsible for this increased thermal sensitivity.